Pengaruh Struktur Modal dan Profitabilitas terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Rahmad Dany Sahputra (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the effect of Capital Structure and Profitability on Firm Value with Financial Performance as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020 2024 using the Purpose Sampling method. The analytical method in this study is multiple linear regression analysis. The results of this study determine that Capital Structure has a negative effect on financial performance. Profitability does not affect financial performance. Capital structure does not affect Firm Value. Profitability has a positive effect on financial performance. Financial performance does not affect Firm Value. Financial performance is unable to mediate the effect of Capital Structure on Firm Value. Financial performance is unable to mediate the effect of Profitability on Firm Value in manufacturing companies in the consumer non-cyclical sector of the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in 2020-2024.